2012
DOI: 10.1093/geront/gns036
|View full text |Cite
|
Sign up to set email alerts
|

Use of Adult Day Care Centers: Do They Offset Utilization of Health Care Services?

Abstract: The current form of ADCC in Israel focuses mainly on meeting social needs of the participants and therefore do not meet the their actual health needs. Therefore, inclusion of health services within ADCC may have an offset effect, but this necessitates further examination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…ADCCs also provide physiotherapy, occupational therapy, nursing care and dietary supervision. Additional services such as showering, shaving, or pedicure can be purchased at extra fees ( Iecovich & Biderman, 2012b ).…”
Section: Formal Settings To Potentially Alleviate Loneliness and Incrmentioning
confidence: 99%
“…ADCCs also provide physiotherapy, occupational therapy, nursing care and dietary supervision. Additional services such as showering, shaving, or pedicure can be purchased at extra fees ( Iecovich & Biderman, 2012b ).…”
Section: Formal Settings To Potentially Alleviate Loneliness and Incrmentioning
confidence: 99%
“…Some studies have failed to demonstrate clearly positive outcomes [24, 25], but others suggest that these programs may enhance quality of life and reduce stress [26, 27]. …”
Section: Examples Of Services and Supports Provided By Community-bmentioning
confidence: 99%
“…Consistently, attending day programs at senior centers has also been found to delay institutional and nursing home placement [23,24] as well as improving wellbeing and mental wellness and reducing depression rates [19]. Ron [25] found that regular attendance to senior centers contributed to the selfesteem of older females, while Iecovich and Biderman [26] found that users of adult day care centers had significant quality of life benefits but found no evidence that users of senior centers used less health services compared with nonusers [27].…”
Section: Introductionmentioning
confidence: 99%